2004
DOI: 10.1074/jbc.m313738200
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Epidermal Growth Factor Receptor Function in the Human Parasitic Helminth Schistosoma mansoni

Abstract: The epidermal growth factor receptor (EGF-R) plays an important role in development and cell differentiation, and homologues of EGF-R have been identified in a broad range of vertebrate and invertebrate organisms. This work concerns the functional characterization of SER, the EGF-R-like molecule previously identified in the helminth parasite Schistosoma mansoni The epidermal growth factor receptor (EGF-R) 1 is a major key mediator of cell communication during animal development and homeostasis. EGF-R was the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 30 publications
5
122
0
Order By: Relevance
“…Similar observations have been made in the S. mansoni model, incubation of parasites with human EGF increasing protein and DNA synthesis as well as protein phosphorylation in larval stages [38]. Therefore, as already proposed for the growth factor TGF-b, a potential role of EGF and of its transduction cascades in the regulation of host-parasite relationships can be considered.…”
Section: Conserved Egf Signalling In Parasitic Helminthssupporting
confidence: 58%
See 1 more Smart Citation
“…Similar observations have been made in the S. mansoni model, incubation of parasites with human EGF increasing protein and DNA synthesis as well as protein phosphorylation in larval stages [38]. Therefore, as already proposed for the growth factor TGF-b, a potential role of EGF and of its transduction cascades in the regulation of host-parasite relationships can be considered.…”
Section: Conserved Egf Signalling In Parasitic Helminthssupporting
confidence: 58%
“…Recent studies on the functional activity of EGF-R in S. mansoni confirmed the conservation of EGF signalling in this parasite [38]. The epidermal growth factor receptor (EGF-R) is a major key mediator of cell communication during animal development and homeostasis.…”
Section: Conserved Egf Signalling In Parasitic Helminthsmentioning
confidence: 95%
“…Such phosphorylation has been shown to be modulated in host-parasite systems during processes as diverse as host cell invasion (Neira et al 2002) and growth factor cross-talk (Vicogne et al 2004), and in response to other host-derived molecular cues Marcila et al 2004). Although relatively few signalling enzymes have been characterized in schistosomes, recent studies have identified several receptor and nonreceptor PTKs in S. mansoni.…”
Section: Introductionmentioning
confidence: 99%
“…Preparations of Xenopus oocytes and microinjection experiments were performed as previously described (Vicogne et al, 2004). In each assay, 20 oocytes removed from at least two to three different animals were microinjected with different concentrations of OA, sera anti-PP1 antibodies, PfLRR1 cRNA or Grb2 P49L cRNA.…”
Section: Preparation Of Pflrr1 Crna and Microinjection To Xenopus Oocmentioning
confidence: 99%